CleanSky 2/Clean Aviation Large passenger aircraft for more sustainable commercial fuselage technologies - Major achievements - Roth, Y.C.; Herrmann, R.; Sanchez Santos, C.; Uellendahl, M.; Koopman, J.; Henneberg, A.; Kos, J.; Villegas, I.F.; Choudhary, A.; Larsen, L.; Ferstl, S.; Diehl, B.; et al. (ICAS, 2024)
In the framework of CleanSky2 (CS2) - Large Passenger Aircraft project, a consortium led by Airbus consisting of universities, research centers and industrial partners across Europe investigated various fuselage system, cabin & airframe technologies for commercial aircraft. The goal has been to strongly contribute to the environmental objectives of 20-30% CO2 reduction whereas at the same time performance increase through weight reduction and improved competitiveness through less recurring cost and industrial ramp up capabilities had to be demonstrated. In total, more than 40 different technologies have been further developed by the European consortium consisting of 14 partners in order to finally deliver an 8m large scale flagship in 2024: the Multifunctional Fuselage Demonstrator. Novel fuselage design and built concepts are demonstrated as well as thermoplastic composite material testing & modelling, elementary parts manufacture and assembly for large scale fuselage structures incl. “zero airframe customization” concepts for cabin installation. Final results and major achievements of this European funded program will be presented and discussed in this paper.